The changing role of collecting societies in the internet - Sebastian Haunss (Internet Policy Review, 2013)
Collecting societies currently face major challenges stemming from: the reconfiguration of existing and emergence of new powerful players in the field of music distribution; the necessity of cross-territorial licensing options, and; the fragmentation of copyrights. This article presents an overview of recent technical and policy developments in this area in Europe and, on a more abstract level, it discusses structural problems underlying the policy conflicts.
Keywords: 300; Copyright; License; Intermediaries; Music; Distribution; Intellectual property rights; Collecting societies; European Union